Teaching Phrasal Verbs in EFL Classes with HIIT Method - Umarova Dilafruz Razzakberdiyevna (Zien Journals, 2024)
This article explores the effectiveness of integrating the High-Intensity Interval Training (HIIT) method into English as a Foreign Language (EFL) classes for teaching phrasal verbs. The study investigates the impact of the HIIT approach on students' acquisition and usage of phrasal verbs, employing a mixedmethods research design. The findings indicate that the HIIT method enhances phrasal verb learning, leading to improved understanding, retention, and application of these challenging language components. The article concludes with implications for EFL educators seeking innovative approaches to enhance phrasal verb instruction.
Keywords: Phrasal verbs; EFL; HIIT; Quantitative